THE ROLE OF EMOTION AND IMAGINATION IN ROMANTICISM - Eldorbek Erkin og’li Khamitov; Markabaeva Mexriban Keulimjayevna (Ta’lim innovatsiyasi va integratsiyasi, 2026)
Abstract This paper examines the significant role of emotion and imagination in Romantic literature. Romanticism, which developed in the late 18th and early 19th centuries, focused on individual feelings, personal experiences, and the creative power of the imagination. Unlike previous literary movements that emphasized logic and reason, Romantic writers valued emotions as a source of inspiration, truth, and artistic expression. Their works often explore the connection between human feelings, nature, and creativity. Emotion is a central element in Romantic literature. Writers depict strong and deep feelings such as love, sorrow, happiness, and despair, allowing readers to understand the inner world of the characters. Emotions are not only used to describe personal experiences but also to reflect on social issues, moral questions, and the human condition. Romantic writers believed that literature gains authenticity and power when it expresses true emotions. Imagination is another core aspect of Romanticism. Through imagination, writers explore abstract ideas, create symbolic and fantastical worlds, and express thoughts beyond everyday life. Imagination is used to depict nature, dreams, fantasy, and even supernatural elements, providing readers with a rich and meaningful understanding of human experiences. It allows writers to go beyond reality, reflect creatively, and convey deep emotional truths. The relationship between emotion and imagination is especially important in Romantic literature. Emotions inspire creativity, while imagination gives structure and meaning to feelings. Together, they create expressive and memorable narratives that explore human psychology, ethical questions, and the beauty of the world. Romantic writers also stress individuality, personal freedom, and authenticity, showing characters who follow their hearts and seek personal truth. In conclusion, emotion and imagination are essential components of Romanticism. Romantic literature highlights the importance of personal experience, creativity, and feelings, providing readers with a deeper understanding of human nature and the mind. By combining emotion with imagination, Romantic writers produce literature that is moving, reflective, and inspiring, encouraging readers to connect with their own emotions, think creatively, and appreciate the beauty and complexity of life.